2012
DOI: 10.1002/pen.23087
|View full text |Cite
|
Sign up to set email alerts
|

Extruded foams from microbial poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) and its blends with cellulose acetate butyrate

Abstract: Extrusion foaming of poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV) and two blends of PHBV with cellulose acetate butyrate (CAB) were studied using an azodicarbonamide (AZ) blowing agent and a single‐screw extruder. The concentration of the blowing agent was systematically varied from 0 to 4.0 phr to achieve maximum density reduction reaching 41%, as well as to obtain information on the dependence of cell growth on blowing agent concentration. Extruded foams were characterized in terms of their bulk densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…Liao et al previously found that the bulk density of PHBV foamed with AZ began to increase after 1.5 phr and suggested this was due to the known poor melt strength. Figure compares the results by Liao et al with those achieved by using higher screw speeds to maintain higher pressures.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Liao et al previously found that the bulk density of PHBV foamed with AZ began to increase after 1.5 phr and suggested this was due to the known poor melt strength. Figure compares the results by Liao et al with those achieved by using higher screw speeds to maintain higher pressures.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce cost as well as expand to broader applications, it is attractive to foam PHAs and PLA. However, attempts at foaming PHAs have seen limited success and require additives or blend components for improvement . The reason has primarily been attributed to poor melt strength and poor elongational viscosity associated with the linear polymers .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations